Tanggung Jawab Perusahaan Dalam Komersialisasi Ruang Angkasa dan Implikasinya Terhadap Outer Space Treaty 1967 (Studi Tentang Wisata Ruang Angkasa) - Tyasworo, Niken; Jumena, Mas Nana (Uti Possidetis: Journal of International Law, 2021)
The exploratory utilization of outer space is currently take a place following the development of science and technologies. At first, the exploration was done by government only, in this time, private companies also take part to do the outer space exploration.The outer space tour activities is one form of outer space commercialization. This time, those activities is still in the developing process for the better future business, especially in the law aspect for the outer space tour activities. So that, an explanation of the outer space tour activity is one particular part that should be extremely clear and understandable for the sake of tourist’s security. Such as, how far the responsibility is given by government and private companies in case of an accident during the outer space tour activities.The conclusion of this research is to mention that Outer Space Treaty 1967, Rescue Agreement 1968, Liability Convention 1972 and Registration Convention 1975 are all be able to applied as basic law for the outer space tour activities. Therefore, the outer space tour activity is something that could have been done routinely in the future and that makes the laws and regulations must be evident, equitable, and liable in order to ensure comfort and safety for the outer space tourists.